Integrated management approach to business process optimization - Baryshevskyi, A. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Digital transformation requires organizations to improve business processes and adopt new digital capabilities. Many initiatives fail because they are not aligned with strategic objectives. This paper proposes an approach to business process optimization based on integrating strategic management with portfolio, program and project management (SP3M). The method strengthens alignment, improves prioritization and supports consistent implementation of redesigned processes.
Keywords: Integrated management; business; optimization; portfolio; strategic management; project management; strategic goals; decision models